Red Lights : The Lives of Sex Workers in Postsocialist China - Zheng, Tiantian (Book collections on Project MUSE., 2009)
In China today, sex work cannot be untangled from the phenomenon of rural-urban migration, the entertainment industry, and state power. In Red Lights, Tiantian Zheng highlights the urban karaoke bar as the locus at which these three factors intersect and provides a rich account of the lives of karaoke hostesses--a career whose name disguises the sex work and minimizes the surprising influence these women often have as power brokers. Zheng embarked on two years of intensely embedded ethnographic fieldwork in her birthplace, Dalian, a large northeastern Chinese seaport of over six million people.